2022
DOI: 10.22159/ijap.2022.v14s5.04
|View full text |Cite
|
Sign up to set email alerts
|

STABILITY OF OMEGA-3 COMPOUNDS COMPLEX WITH PPAR-γ RECEPTOR AS AN ANTI-OBESITY USING MOLECULAR DYNAMIC SIMULATION

Abstract: Objective: Obesity is a major contributor to comorbid diseases based on low grade chronic inflammation. Omega-3 fatty acids have a role in inflammation so it is thought to prevent obesity. This study was conducted to analyze the stability of omega-3 fatty acids with the PPAR-γ receptor using molecular dynamic simulation to investigate the relationship of macromolecule interactions to biologically relevant as an obesity comorbid. Methods: The methods consisted of ligand acquisition, molecular dynamic simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This study aligns with other research that has demonstrated the stability of omega-3 molecules, including docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and heneicosapentaenoic acid (HPA), using the molecular dynamics modeling approach. Docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and heneicosapentaenoic acid (HPA) can be used as primary therapeutic agents to bind to PPAR-and GPR120 receptors in order to treat and prevent obesity (Musfiroh et al 2021(Musfiroh et al , 2022. The amino acid fluctuations of the two receptor complex systems calculated by RMSF showed the same pattern in all regions.…”
Section: Molecular Dynamic Simulationmentioning
confidence: 99%
“…This study aligns with other research that has demonstrated the stability of omega-3 molecules, including docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and heneicosapentaenoic acid (HPA), using the molecular dynamics modeling approach. Docosahexaenoic acid (DHA), docosapentaenoic acid (DPA), and heneicosapentaenoic acid (HPA) can be used as primary therapeutic agents to bind to PPAR-and GPR120 receptors in order to treat and prevent obesity (Musfiroh et al 2021(Musfiroh et al , 2022. The amino acid fluctuations of the two receptor complex systems calculated by RMSF showed the same pattern in all regions.…”
Section: Molecular Dynamic Simulationmentioning
confidence: 99%